Site‐Specific Encoding of Photoactivity in Antibodies Enables Light‐Mediated Antibody–Antigen Binding on Live Cells. Issue 50 (31st October 2019) - Bridge, Thomas; Shaikh, Saher A.; Thomas, Paul; Botta, Joaquin; McCormick, Peter J.; Sachdeva, Amit
Abstract: Antibodies have found applications in several fields, including, medicine, diagnostics, and nanotechnology, yet methods to modulate antibody–antigen binding using an external agent remain limited. Here, we have developed photoactive antibody fragments by genetic site‐specific replacement of single tyrosine residues with photocaged tyrosine, in an antibody fragment, 7D12. A simple and robust assay is adopted to evaluate the light‐mediated binding of 7D12 mutants to its target, epidermal growth factor receptor (EGFR), on the surface of cancer cells. Presence of photocaged tyrosine reduces 7D12‐EGFR binding affinity by over 20‐fold in two out of three 7D12 mutants studied, and binding is restored upon exposure to 365 nm light. Molecular dynamics simulations explain the difference in effect of photocaging on 7D12‐EGFR interaction among the mutants. Finally, we demonstrate the application of photoactive antibodies in delivering fluorophores to EGFR‐positive live cancer cells in a light‐dependent manner. Abstract : Site‐specific installation of a single photoactive amino acid in an antibody enables development of photoactive antibodies allowing light‐controlled, cell‐specific delivery of small molecules on live cancer cells.